Associations between objective afternoon and evening physical activity and objective sleep in patients with fibromyalgia and insomnia. (29th October 2020) - McGovney, Kevin D.; Curtis, Ashley F.; McCrae, Christina S.
Abstract: Patients with fibromyalgia (FM) suffer from chronic pain, which limits physical activity and is associated with disturbed sleep. However, the relationship between physical activity, pain and sleep is unclear in these patients. This study examined whether actigraphic (Actiwatch‐2, Philips Respironics) afternoon and evening activity and pain are associated with actigraphic sleep. Adults with FM and insomnia complaints ( n  = 160, mean age [ M age ] = 52, SD  = 12, 94% female) completed 14 days of actigraphy. Activity levels (i.e., activity counts per minute) were recorded, and average afternoon/evening activity for intervals 12:00–3:00 PM, 3:00–6:00 PM and 6:00–9:00 PM was computed. Multiple linear regressions examined whether afternoon/evening activity, pain (daily evening diaries from 0 [no pain sensation] to 100 [most intense pain imaginable]), or their interaction, predicted sleep onset latency (SOL), wake time after sleep onset (WASO), total sleep time (TST) and sleep efficiency (SE). Greater afternoon activity was independently associated with lower SE ( B  = −0.08, p  < .001), lower TST ( β  = −0.36, standard error [ SE ] = 0.06, p  < .001) and longer WASO ( B  = 0.34, p  < .001). Greater early evening activity was independently associated with lower SE ( B  = −0.06, p  < .001), lower TST ( β  = −0.26, SE  = 0.06, p  < .001) and longer WASO ( B  = 0.23, p  < .001). Self‐reported pain intensity interacted with afternoon and early evening physical activity, such that associations between higher activity and lower SE were stronger for individuals reporting higher pain. Late evening activity was not associated with sleep outcomes. Results suggest that in FM, increased afternoon and early evening physical activity is associated with sleep disturbance, and this relationship is stronger in individuals with higher pain.